SEJARAH PERKEMBANGAN SEKOLAH DASAR ISLAM AS-SHOFA DI KOTA PEKANBARU 1991-2018 - Fatah, Yendi Abdul; Isjoni, Isjoni; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This thesis is titled "The History of Development of The As-shofa Islamic Primary School in The City of Pekanbaru 1991-2018”. The purpose of this study is to find out (1) How the History of the establishment of the As-Shofa Islamic Elementary School (2) How the Development of the As-Shofa Islamic Elementary School 1991-2018 (3) What are the driving factors and inhibiting factors in the development of the As-Islamic Elementary School shofa 1991-2018 . This study uses a historical approach, data collection methods with field studies in the form of observations and interviews as well as archival and document studies. This research was conducted in As-shofa Elementary School and Pekanbaru city . After the data has been collected, data testing is done by source criticism by testing the source authenticity and comparing data with one another, such as comparing the results of interviews with written evidence. Based on the results of this study it was concluded that the As-Shofa Elementary School was born against the background of the founder's ideals namely Drs. Syafwi H. Khalil, M. Pd in 19 91 on keprihatinanya see the condition of education in Indonesia , especially in the city of Pekanbaru perceived lack equip students with competence and noble spirit and educational quality, Islamic religious grounds . Founder of As-shofa Islamic Primary Schoolhoping to form young generation who are Islamic and have competence, a sense of nationalism and a strong religious base. The results of the research of this thesis are, (1) As-shofa Islamic Elementary School was established in 1991, started by Ustadz Drs. H. Syafwi Khalil, M. Pd along with other friends. (2) As-shofa Islamic Elementary School has developed quite rapidly in recent years, in several aspects such as the number of students and the number of buildings increasing and developing . (3) supporting factors of the As-Shofa Islamic Elementary School are the role of citizens, the government and the basics of the majority of the demands of the community especially the city of Pekanbaru during the early growth of the As-Shofa Islamic Elementary School. the factors which hindered As-shofa Islamic Elementary School were the limitations of the room and the building of learning in the early pioneering period.Key Words: Islamic School, History, Fullday, Pekanbaru